Problematic Issues of Estimated Liabilities in Payroll Accounting - TATYANA YU. Serebryakova (Учёт. Анализ. Аудит, 2019)
The convergence of Russian and international accounting and reporting principles is hindered because of the limitations in the domestic standards in comparison with their international prototypes, which, in fact, leads to distortion of international accounting rules. On the other hand, the academic literature often replicates the findings and recommendations which do not fully reflect the ideas of the international accounting principles, demonstrating the lack of critical approach to the contents and applications of certain provisions of the IFRS in the Russian accounting practice, for example, the estimated obligations in connection with vacation pay. To ensure the harmonization and uniform application of international and Russian rules of accounting it is necessary to apply the principles of accounting of estimated liabilities in respect of employee benefits, required by the IFRS under the same name, taking into consideration that the domestic standard on the estimated liabilities does not contain specific rules about provisions for such expenses